An insider’s guide to political jobs in Washington - Endicott, William T. (John Wiley & Sons, 2003)
BILL ENDICOTT has served in political jobs for three decades. He worked for three congressmen, the Democratic National Committee, and the Clinton Administration. He has written a remarkable description of what Washington political jobs entail, how you get them, and where they lead–a public service.